Complex systems evaluation of fatigue based on ECG interconnected parameters - Vainoras, A.; Venskaityte, E.; Balague, N.; Poderys, J.; Berskiene, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Dynamic processes are evident trough the complex fluctuations of physiologic output signals such as those appearing in the ECG. Interconnections of different ECG parameters based on matrix theory (Vainoras et al., 2008) have been determined during a modified Rufje exercise test. The aim of this investigation was to evaluate the dynamics of different fractal levels of inter-parameter interactions in the ECG and to establish new features to assess fatigue. Methods 14 elite Lithuanian Greco Roman wrestlers participated in the study performing a modified Rufje exercise test in 4 stages of the investigation protocol: 1st day before trainings and after 1st and 2nd training, and 2nd day before trainings. The "Kaunas-load" ECG analysis system has been used for the evaluation (Vainoras, 1997). The interconnection of different ECG parameters representing different fractal levels (heart, organism) have been studied in the different stages. Results The interactions of ECG parameters and its dynamics at different fractal level varied respectively to the stage of investigation. The dynamic of interconnections during the beginning of 1st and 2nd day was similar - the change of interconnection was increasing during load at heart level. In both days the results after the 1st and 2nd training, respectively, show how interconnections at the organism level differ significantly (P>0,95), showing an increase in the fluctuations with fatigue. This significant change also depends on the sportsmen level and experience. Discussion New features of fatigue have been revealed as the tendency to present altered values of inter-parameter relationships in post-training monitoring. These results are in agreement with the finding that the process of fatigue is related to the interaction between functional systems (Nybo, 2008). Summing-up the evaluation of the interconnection between ECG parameters representing different fractal levels allows the detection of fatigue features. References Nybo L. (2008). Hyperthermia and fatigue. Journal of Applied Physiology, 104, 871-878. Vainoras A., Gargasas L., Ruseckas R. et al..Computerized exercise electrocardiogram analysis system "Kaunas-Load". (1997) In "Electrocardiology`97" Bratislava, Slovak R., 253-256. Vainoras A., Navickas Z., Poderys J., Berskiene K., Bikulciene L. (2008). ECG signal for assessment of interpersonal or inter parameter influences. // the 2nd International Scientific Conference "Current issues and new ideas in sport science". [Electronic resource], Kaunas.